If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y + -1x = 5 Reorder the terms: -1x + 1y = 5 Solving -1x + 1y = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. -1x + 1y + -1y = 5 + -1y Combine like terms: 1y + -1y = 0 -1x + 0 = 5 + -1y -1x = 5 + -1y Divide each side by '-1'. x = -5 + y Simplifying x = -5 + y
| 6x+3x-4=-22 | | 5y+3x=475 | | 3/2÷2 | | C(x)=2x^2-32x+690 | | -5-3c=46 | | -5xN=-100 | | -15+.39(269.615)=x | | 200=4x^2+20x | | y-5=.6(x+6) | | 7d+1=4p | | -4p+7=15 | | 5x-2+2x+3-1=9-65 | | 5x+7x+47x=2-1+3 | | 21d=12p-3 | | 9m+5m= | | 5x+2(3x-17)=32 | | 1+4=-3+7 | | 3x+5y=475 | | x^5/3=90 | | y-5=1.66(x+6) | | -57+4x=-8+11x | | 7/9x=2/5 | | 4=4t | | |.01=x/16 | | -63+42x=357 | | -5y=-55x+40 | | 2x=8y+4 | | 14.95+.13(166.666)=x | | h=8+23t-16t^2 | | -y=-4x+57 | | 5x+7(6x-17)=163 | | 2t-6=5t |